Prospective clinical and DaT-SPECT imaging in premotor LRRK2 G2019S-associated Parkinson disease. (1st August 2017) - Sierra, María; Martínez-Rodríguez, Isabel; Sánchez-Juan, Pascual; González-Aramburu, Isabel; Jiménez-Alonso, Mikel; Sánchez-Rodríguez, Antonio; Berciano, José; Banzo, Ignacio; Infante, Jon
Abstract : Objective: To assess the value of baseline clinical and imaging biomarkers in a cohort of asymptomatic LRRK2 G2019S carriers for predicting conversion to Parkinson disease (PD) at 4 years. Methods: Thirty-two asymptomatic carriers of LRRK2 G2019S mutation underwent baseline and 4-year evaluation including clinical examination (Unified Parkinson's Disease Rating Scale, part III, olfaction University of Pennsylvania Smell Identification Test [UPSIT]) and dopamine transporter (DaT) SPECT ( 123 I-ioflupane). Visual and semiquantitative analysis of images was performed. The specific striatal binding ratio was calculated (striatal region of interest [ROI] − occipital ROI/occipital ROI). Results: Three carriers, asymptomatic at baseline, had converted to PD at 4-year evaluation. Twenty-three participants were fully evaluated. PD converters had lower striatal DaT binding at baseline than nonconverters ( p = 0.002). A baseline scan with a ratio of bilateral striatal uptake below 1 predicted conversion to PD within the 4-year period with high sensitivity and specificity (area under the curve 1; p = 0.006). The slope of DaT binding decline between the 2 scans was similar in PD converters and nonconverters. Age-adjusted UPSIT score at baseline and at 4 years was similar in both groups. Conclusions: Semiquantitative DaT-SPECT could be used to predict early conversion to PD in asymptomatic carriers of the LRRK2 G2019S mutation. Rate of conversion to PD at 4 years in this cohort aged ∼64 years was 12%. The slope of DaT binding decline on DaT-SPECT imaging seems to be similar across different stages of the premotor period.